2020
DOI: 10.3390/ijerph17155427
|View full text |Cite
|
Sign up to set email alerts
|

Maternal–Infant Bonding and Its Relationships with Maternal Depressive Symptoms, Stress and Anxiety in the Early Postpartum Period in a Polish Sample

Abstract: A large body of literature indicates that there is a relationship between maternal psychological well-being and the early maternal–infant bond. However, this relationship is not fully understood, due to the different theoretical frameworks of maternal–infant bonding and different data collections points. Thus, the aim of this study was to examine the relationship between the maternal bond and the maternal psychological state including anxiety, stress, and maternal depressive symptoms. In this cohort study, 150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 39 publications
(66 reference statements)
4
57
2
3
Order By: Relevance
“…In a multiple regression analysis, however, the association between symptoms of anxiety and mother–infant bonding was not significant after controlling for the effect of depressive symptoms. Lutkiewicz et al 11 also reported similar results in 150 Polish mothers at 1–3 days after childbirth. These inconsistencies among studies may stem from differences in ethnicity, postpartum period, rating scale and statistical analysis.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In a multiple regression analysis, however, the association between symptoms of anxiety and mother–infant bonding was not significant after controlling for the effect of depressive symptoms. Lutkiewicz et al 11 also reported similar results in 150 Polish mothers at 1–3 days after childbirth. These inconsistencies among studies may stem from differences in ethnicity, postpartum period, rating scale and statistical analysis.…”
Section: Discussionmentioning
confidence: 57%
“…7,8,15,16,18,21 The Edinburgh Postnatal Depression Scale (EPDS) is the most widely used self-report questionnaire for screening for peripartum depression. 6,[9][10][11]13,[15][16][17][18][19][23][24][25] However, this scale is not suitable for detecting peripartum anxiety. 23 We therefore used the Hospital Anxiety and Depression Scale (HADS), which is a self-report questionnaire designed to identify anxiety and depression in nonpsychiatric hospital outpatients.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…A father's mental health during the antenatal and postpartum periods is a relatively under-researched topic in comparison with maternal mental health at that time (Ilska and Przybyła-Basista, 2014;Kucharska, 2020;Lutkiewicz et al, 2020). The prevalence of perinatal depression among fathers has been shown to be about 10% at the very beginning of pregnancy increasing to 25% around 6 months after birth (Paulson and Bazemore, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The prenatal depression experienced by pregnant women has various negative consequences for the wellbeing of the woman, her partner, family, and the birth and development of the child [ 5 ]. Furthermore, it increases the risk of postnatal depression [ 6 , 7 ], the consequences of which may be particularly unfavorable for the mother–infant relationship, namely, lower intensity of emotional attachment to the child, adverse effects on the mother–child relationship, delays in cognitive/emotional development of the infant, and behavioral problems in later childhood [ 3 , 8 , 9 , 10 , 11 , 12 , 13 ]. Focusing on the consequences of postnatal depression and its risk factors was the subject of many studies [ 4 , 5 , 10 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%